2002
DOI: 10.1038/sj.bjc.6600415
|View full text |Cite
|
Sign up to set email alerts
|

Dietary factors and stomach cancer mortality

Abstract: The present study examined the relationship between stomach cancer and the low intake of fresh fruit and vegetables and/or a high intake of pickled, preserved or salted foods and frequent use of cooking oil. During 139 390 person -year of follow-up of over 13 000 subjects, 116 died from stomach cancer. Using a Cox proportional hazards -regression analysis of relative risk (RR, 95% CI) controlling for age, sex, smoking and other dietary factors, a significant decline was found with a high consumption of green a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
84
4

Year Published

2004
2004
2014
2014

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 135 publications
(93 citation statements)
references
References 46 publications
5
84
4
Order By: Relevance
“…Earlier epidemiological studies on esophageal and gastric carcinoma in Kashmir suggest that the special dietary habits of Kashmiri population could be the most likely etiological factors for the development of stomach cancer (Khuroo et al, 1992;Malik et al, 2000). A study reported that high consumption of pickled foods was associated with a significant increased risk of stomach cancer (Ngoan et al, 2002). However, in the present study, traditional pickle consumption did not show any significant association with any of the gene methylations in any age group of patients.…”
Section: Discussioncontrasting
confidence: 92%
“…Earlier epidemiological studies on esophageal and gastric carcinoma in Kashmir suggest that the special dietary habits of Kashmiri population could be the most likely etiological factors for the development of stomach cancer (Khuroo et al, 1992;Malik et al, 2000). A study reported that high consumption of pickled foods was associated with a significant increased risk of stomach cancer (Ngoan et al, 2002). However, in the present study, traditional pickle consumption did not show any significant association with any of the gene methylations in any age group of patients.…”
Section: Discussioncontrasting
confidence: 92%
“…Ngoan and colleagues examined 13 000 Japanese men and women and identifi ed 116 gastric cancer deaths during a 10-year follow-up. Higher consumption of pickled foods and traditional soups were associated with increased risk, although without statistical signifi cance [24].…”
Section: Evidence From Cohort Studiesmentioning
confidence: 93%
“…Depending on the available data, the reference groups included study subjects with no or the lowest amount of pickled vegetable/food consumption. One cohort study reported results separately for all cancer cases and also after excluding cases diagnosed during the first 3 years of follow-up (69); only the latter results were included in this meta-analysis. A study conducted in Japan (17) reported data from 2 regions, one affected by atomic bomb and one not affected; only the results from the latter were considered in our analysis.…”
Section: Data Extraction and Statistical Analysismentioning
confidence: 99%